The metaphor of knowledge in Arabic proverbs in walls of pesantren - Fatkhullah, Faiz; Hanafiah, Hanafiah; Farhan, Farhan (Universitas Mulawarman, 2025)
This article examines the conceptual representation of knowledge in Arabic proverbs mahfuzhat displayed on the walls of two Indonesian Islamic boarding schools (pesantren): Condong and Al-Bahjah. Employing Lakoff and Johnson’s conceptual metaphor theory and a descriptive-analytical qualitative approach, the study analyzes 10 Arabic proverbs collected through field observation, documentation, and semi-structured interviews. The findings reveal that knowledge is metaphorized as light, spiritual adornment, the path to paradise, fruitful trees, and a defining feature of humanity. These metaphors illustrate how mahfuzhat function not merely as decorative or rhetorical devices, but as pedagogical tools that foster character, discipline, and reverence for knowledge in pesantren education. The study highlights the educational and moral significance of Arabic proverbs as cultural texts and demonstrates their role in shaping the intellectual and spiritual formation of santri. This research contributes to the growing discourse on metaphor and education by foregrounding mahfuzhat as a distinct source of Islamic educational values, often overlooked in metaphor studies.